Improving Reversible Capacities of High-Surface Lithium Insertion Materials – The Case of Amorphous TiO2 - Ganapathy, Swapna; Basak, Shibabrata; Lefering, Anton; Rogers, Edith; Zandbergen, Henny W.; Wagemaker, Marnix (Frontiers in Energy Research, 2014)
Chemisorbed water and solvent molecules and their reactivity with components from the electrolyte in high-surface nanostructured electrodes remains a contributing factor towards capacity diminishment on cycling in lithium ion batteries due to the limit in maximum annealing temperature. Here we report a marked improvement in the capacity retention of amorphous TiO2 by the choice of preparation solvent, control of annealing temperature and the presence of surface functional groups. Careful heating of the amorphous TiO2 sample prepared in acetone under vacuum lead to complete removal of all molecular solvent and an improved capacity retention of 220 mAh/g over 50 cycles at a C/10 rate. Amorphous TiO2 when prepared in ethanol and heated under vacuum showed an even better capacity retention of 240 mAh/g. From FTIR Spectroscopy and Electron Energy Loss Spectroscopy measurements, the improved capacity is attributed to the complete removal of ethanol and the presence of very small fractions of residual functional groups coordinated to oxygen-deficient surface titanium sites. These displace the more reactive chemisorbed hydroxyl groups, limiting reaction with components from the electrolyte and possibly enhancing the integrity of the solid electrolyte interface (SEI). The present research provides a facile strategy to improve the capacity retention of nanostructured electrode materials.